Coregonus sardinella Valenciennes 1848 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Coregonus sardinella Valenciennes, 1848. Least Cisco. To 47 cm (18.3 in) TL (Page and Burr 1991). Bering Strait and Siberia west to White Sea; Arctic coasts of Alaska east to Rasmussen Basin and Chantrey Inlet, King William Island, Nunuvut (Reist in Coad and Reist 2018) [records further east are without documentation—Reist in Coad and Reist 2018] and south to Bristol Bay, Bering Sea (Mecklenburg et al. 2002). Coastal waters near shore and fresh water. Anadromous and landlocked populations (Mecklenburg et al. 2002). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 53, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...